To solve the equation for y, we can start by multiplying both sides of the equation by 5y+3:
(-1)(5y+3)/(5y+3) = -7(5y+3)/(5y+3)
This simplifies to:
-1 = -35y - 21
Next, we can isolate the y term by moving -21 to the other side of the equation:
35y = -21 + 1
35y = -20
Finally, we divide both sides of the equation by 35 to solve for y:
y = -20/35
Simplified, this is:
y = -4/7
Therefore, the solution for y is -4/7.
None of the provided answer choices match this result.
Solve the equation for y.
−1 over 5y+3=−7
50
-35
15
55
1 answer